2017
DOI: 10.31228/osf.io/3gks7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crime and Governance in Indian Country

Abstract: Criminal jurisdiction in Indian country is defined by a central, ironic paradox. Recent federal laws expanding tribal criminal jurisdiction are, in many respects, enormous victories for Indian country, as they acknowledge and reify a more robust notion of tribal sovereignty, one capable of accommodating increased tribal control over safety and security on Indian reservations. At the same time, the laws make clear that sovereignty comes at a price, potentially working to effectuate further assimilation of triba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…156 In her analysis about the implementation of VAWA 2013, Professor Angela Riley also acknowledged the problems with making constitutional provisions applicable to Indian tribes. 157 However, she concluded that some constitutional provisions could be applied to Indian tribes without jeopardizing their cultural and political distinctiveness. First, she noted that a lot of existing tribal court procedures are already similar if not identical to the ones applied in federal and state courts.…”
Section: A Critique Of These Three Proposals: Indian Tribes Should Nomentioning
confidence: 99%
“…156 In her analysis about the implementation of VAWA 2013, Professor Angela Riley also acknowledged the problems with making constitutional provisions applicable to Indian tribes. 157 However, she concluded that some constitutional provisions could be applied to Indian tribes without jeopardizing their cultural and political distinctiveness. First, she noted that a lot of existing tribal court procedures are already similar if not identical to the ones applied in federal and state courts.…”
Section: A Critique Of These Three Proposals: Indian Tribes Should Nomentioning
confidence: 99%
“…Since 1999, the United States government has acknowledged that Native people suffer the highest per capita rates of violent crime in the nation (Bureau of Justice Statistics 1999, 2004; Rosay 2016). Empirical studies of rates of victimization in the United States almost universally conclude that Native people suffer violence at extremely elevated rates when compared to the general population (Bachman et al, 2010; Black et al, 2010; Riley 2016). Domestic violence and sexual assault, in particular, are very common in the lives of Native women (Oetzel and Duran, 2004; Sapra et al, 2014).…”
Section: Statisticsmentioning
confidence: 99%
“…The Court ruled that tribal nations are forbidden to prosecute non-Indians for any crime, no matter how heinous. Oliphant v. Suquamish Indian Tribe ushered a strangely racialized form of determining a criminal jurisdiction question (Riley 2016).…”
Section: Jurisdictionmentioning
confidence: 99%
See 2 more Smart Citations